A THEORETICAL ARCHITECTURE FOR DECENTRALIZED URBAN SYSTEMS IN THE POST-DIGITAL ERA - Amos Lukas (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2025)
This study proposes a theoretical architecture for decentralized urban systems in the post-digital era, characterized by the seamless integration of digital technologies into everyday urban life. It addresses the limitations of centralized urban governance models, which often struggle with scalability, resilience, and inclusive participation in rapidly evolving cities. By synthesizing interdisciplinary perspectives from urban studies, distributed systems, and socio-technical theory, the research develops a conceptual framework that redefines urban systems as adaptive, networked, and citizen-centric ecosystems. Using a descriptive qualitative approach, this study analyzes existing literature and emerging practices related to decentralization, including blockchain governance, edge computing, and participatory digital platforms. The findings reveal that effective decentralized urban systems operate through three interdependent layers: infrastructural decentralization, governance decentralization, and cognitive decentralization. These layers interact dynamically through feedback mechanisms enabled by real-time data exchange and digital connectivity. The proposed architecture highlights how decentralization enhances urban resilience by reducing dependency on centralized infrastructures, improves service efficiency through localized decision-making, and promotes inclusivity by empowering citizens as active contributors to urban governance. However, the study also identifies key challenges, including technological interoperability, regulatory constraints, and digital inequality. This research contributes to the theoretical advancement of post-digital urbanism by offering a comprehensive and integrative model that bridges technological innovation with social and institutional dimensions. The study concludes that decentralized urban systems represent a transformative paradigm for building sustainable, adaptive, and democratic cities, and provides a foundation for future empirical validation and policy development.